Fostering Entrepreneurial Spirit: The Impact of the 'Kantin Kejujuran' Program on OSIS Members in SMP YBPK Kota Kediri - Machful Indrakurniawan; Mahardika Darmawan Kusuma Wardana; Ria Wulandari (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article presents the results and implications of the